Analysis of Serum Testosterone Levels by Gender and Age Group in a Sample Population attended at a tertiary centre, Bangladesh (Bangladesh Journal of Medicine, 2026)
Background: Testosterone is an important androgen influencing reproductive and metabolic health. This study describes serum testosterone levels by gender and age group among individuals attending Institute of Nuclear Medicine and Allied Sciences( INMAS), Sylhet, Bangladesh. Methods: A crosssectional analysis of anonymized data of total 420 patients were included in this study who were referred to INMAS, Sylhet for serum testosterone levels assay from July 2023 to June 2025. Variables were age, gender, and serum testosterone level. Serum testosterone levels weremeasured in ng/dL unit. Descriptive statistics, group means, and Pearson correlation were computed. Results: Mean age was 32.47 ± 11.87 years (range 6–70). Mean testosterone was 339.63± 243.82 (range 0.10–1052.72). Males showed higher mean testosterone than females. Mean testosterone by age group (mean ± SD):=60: 351.64 (n=11). Correlation between age and testosterone: r = 0.29. Conclusion: Testosterone levels vary by gender and age group in this sample. These descriptive data support establishing local reference values and further analytic studies in the Bangladeshi population.Bangladesh J Medicine 2026; 37(1): 58-61